Perancangan Alat Pencetak Intip Baru Dengan Menggunakan Metode Ergonomic Function Deployment - Keriswanto, Tatag, Siti Nandiroh, ST. M.Eng (2016)
Usaha Mikro Kecil dan Menenengah (UMKM) is an industrial business activities, operated a small group of people with limited capital capability. One of them SMEs engaged in the production encountered some problems intip disolo produski process. One of the problems dalah display devices such ergonomis.ngan intip less. Therefore, the need for repairs to fix with the design of display devices are more ergonomic than before, so that the production process can peek over was smooth and can meet consumer demand for food that is typical of the city of Surakarta is intip. The design of display devices peep new, more ergonomic and productive using Ergonomic Function Deployment (EFD). So that the design can be a tool when realisasikan display devices peep more ergonomic and better than the previous peek display devices. The results showed that of the 24 UMKM Peek region of Surakarta want display devices intip who has atrribut: dimensions kendil must be in conformity with the size of the intip big that 18cm, performance display devices intip new ones should be better than the previous tool, price display devices intip affordable, and tools Printers intip has ergonomic concept that ENASE (Effectively, comfortable, safe, Healthy and Efficient) that are safe and comfortable when in use. With a desire on the part of UMKM obtained attributes and product design matching with the UMKM wishes and given the name "Tatag Kendil". Dimensions Tatag kendil can result in intip in size 18 cm. Tatag kendil more productive time intipnya hacking process, more ergonomic and affordable price. Keywords: Ergonomic Function Deployment, UMKM Intip, ENASE.